Formulation and Evaluation of Timed Delayed Capsule Device for Chronotherapeutic Delivery of Terbutaline Sulphate - Mahajan, AN; Pancholi, SS (Ars Pharmaceutica (Internet), 2009)
The aim of the present study was to develop timed delayed capsule device of terbutaline sulphate intended for chronotherapy. A time delayed capsule was prepared by sealing the drug tablet and the expulsion excipient inside the insoluble hard gelatin capsule body with erodible tablet plug. The erodible tablets were prepared by direct compression. Influence of formulation factors such as type of plug material, different plug composition, erodible tablet weight and hardness was investigated to characterize the lag time (t10). The results indicated that drug release from the time delayed capsule exhibited an initial lag period, followed by a stage of rapid drug release. Erodible tablet plugs prepared using higher molecular weight of polyethylene oxide resulted in longer lag times. A good correlation was observed between erodible tablet weight and lag time. In accordance with the chronomodulated therapy of asthma the lag time criterion of 5hrs was satisfied by formulation containing 90mg of WSR N-10 (low molecular weight polyethylene oxide) in the erodible tablet plug.